Online crowdfunding platforms in European Union - Sheiko, I. A.; Murzabulatova, O. V.; Obeid Lara Hodor (ХНУРЕ, 2022)
Crowdfunding platforms are online platforms that enable interaction between fundraisers and the crowd (investors). Financial pledges can be made and collected through the crowdfunding platform. Fundraisers are usually charged a fee by crowdfunding platforms if the fundraising campaign has been successful. In return, crowdfunding platforms are expected to provide a secure and easy to use service
Keywords: crowdfunding platform; financial pledges